Prognostic value of disease risk score versus gait speed in older adults with lymphoma. Issue 12 (15th October 2021) - Mozessohn, Lee; Zhang, Liying; Odejide, Oreofe O.; Chen, Richard; Buckstein, Rena; Soiffer, Robert J.; Castillo, Jorge J.; Driver, Jane A.; Abel, Gregory A.
Abstract: Measures of physical function predict survival in older patients with lymphoma but their prognostic ability has not been compared to disease-specific risk scores. We prospectively recruited patients ≥75 years with lymphoma. Patients underwent a frailty screen including 4-m gait speed. Disease-specific risk scores were obtained retrospectively. Among 168 patients, there was no association between disease-specific risk score and survival. Conversely, faster gait speed was significantly associated with survival in the entire cohort (HR = 0.16; 95%CI, 0.06–0.42; p = 0.0003) indicating a HR of 0.63 for an increase in gait speed of 0.25 m/s. When gait speed was added to the DLBCL IPI and FLIPI separately, it was significantly associated with OS ( p = 0.004 for DLBCL, p = 0.03 for FLIPI) which increased its predictive power. Our study of older lymphoma patients demonstrates gait speed may improve outcome prediction beyond standard prognostic scores.